Kettles of hawks: public opinion on the nuclear taboo and noncombatant immunity in the United States, United Kingdom, France, and Israel - Dill, J; Sagan, SD; Valentino, BA (Taylor and Francis, 2022)
Recent scholarship has established that a majority of Americans will support the use of nuclear weapons and violate the principle of noncombatant immunity when American lives are on the line. Some scholars contend, however, that these hawkish American attitudes are an outlier and that other Western democratic publics have more fully internalized the nuclear taboo, as well as the prohibition on deliberately killing civilians. To investigate cross-national attitudes on these important norms, we conducted a survey experiment of American, British, French, and Israeli citizens. We find that American attitudes are not exceptional. Rather, Israeli respondents display the most hawkish preferences; French and American citizens are roughly equally hawkish; and the British public is consistently the least supportive of nuclear use or targeting civilians. Categorical prohibitions—against nuclear use and targeting civilians—do little to shape public opinion in these four countries. Instead, public opinion in each state follows the same consequentialist logic: a majority or near majority of respondents are willing to support using nuclear weapons when they are more effective than conventional options, but support declines when collateral civilian deaths rise. Respondents’ preferences for compatriots over foreign civilians and respondents’ retributiveness help explain individual-level variation in attitudes.